Actividades de Enriquecimento Curricular na opinião de Pais e Professores. - Moreira, Lurdes (2012)
A educação inclusiva tem vindo a afirmar-se como um movimento educativo que permite criar igualdade de oportunidades para todas as crianças. Para que tal aconteça é fulcral que os professores que actuam em salas de aula do ensino regular tenham acesso a métodos, estratégias e técnicas que lhes permitam uma acção educativa inclusiva e, simultaneamente, promotora do potencial académico, emocional e social. Torna-se assim importante determinar as necessidades de formação dos professores, na medida em que estes lidam com uma vasta variedade de crianças a cujas necessidades distintas têm de dar respostas que se pretendem eficazes. O trabalho que se apresenta corresponde a uma parte da pesquisa realizada no âmbito do Projecto Comenius DISTINC (Developing an In Service Training for Inclusive Pratices) e centra-se nos resultados obtidos relativamente a um questionário passado em 2011 a 50 professores do 1.º Ciclo do Ensino Básico da região do Alentejo. O questionário permitiu identificar necessidades de formação no âmbito das dificuldades de aprendizagem (em diversos domínios) e dos comportamentos desafiantes na medida em que estes se relacionam com a aprendizagem e o sucesso escolar da criança. Abstract Education policies should be primarily designed to ensure students conditions to acquire knowledge and develop skills to better exercise citizenship and participate in social, political and economic activities. The Enrichment Extracurricular Activities is a priority goal of the Portuguese Government to improve teaching and learning conditions in the first cycle of basic education (primary school) and to implement the concept of "full time school." The Enrichment Extracurricular Activities (EEA) respond to this educational policy and seek to promote social justice as long as generalize a set of activities previously available only to children attending the Leisure Activities Program (LAP). In this sense, EEA pretend to fulfill the dual purpose of ensuring that all students in the first years of school have access to a set of free enriching learning activities and at the same time it deals with the priority set out by the Government to promote social responses in the field of family support. Although there is a consensus that the EEA under the program "School Full Time" is socially relevant for many families the program has failed to meet consensus regarding its pedagogical relevance and adequacy and did not respond to some of the expectations created about activities quality in respect to specific teachers training. The aim of this paper is therefore showing parents and teachers opinions about the importance, organization and development of EEA. Data were collected through a survey questionnaire with open and closed questions and analyzed through qualitative and statistical procedures. This communication present the opinion of parents about the EEA. Keywords: Enrichment Extracurricular Activities, opinions, importance, organization, development.